Energy Saving Opportunities in 3-Phase Induction Motors with Variable Speed Drive (V.S.D.) Drives - Rachmadita, Renanda Nia; Rahman, Farhan Wahyu Nur; Setiawan, Edy; Juniani, Anda Iviana; Wiediartini, Wiediartini; Satrianata, Lugas Jagad (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2024)
Most of the load in the motorcycles industry is motors. So, the largest energy use is in motorcycles. This study aims to prove the effect of speed change on a three-phase induction motor on energy consumption with a V.S.D. drive. The method used in this proof uses direct experiment methods and data analysis. The relationship between speed and energy use can be demonstrated through testing and data analysis. The results show that V.S.D. is set at frequencies of 20 Hz and 40 Hz to regulate the speed of the motor as a pump drive can save its energy use. This resulted in a reduction in energy consumption of 20.54% and operational costs of up to Rp 3,292.32 per month in the implementation of the motor as a pump driver.Bahasa IndonesiaSebagian besar beban di industri adalah motor. Sehingga penggunaan energi terbesar adalah pada penggunaan motor. Penelitian ini untuk membuktikan pengaruh perubahan kecepatan pada motor induksi tiga fase terhadap konsumsi energi dengan penggerak VSD. Metode yang digunakan dalam pembuktian ini menggunakan metode eksperimen langsung dan analisa data. Melalui pengujian dan analisis data, hubungan antara kecepatan dan penggunaan energi dapat ditunjukkan. Hasilnya menunjukkan bahwa VSD di atur pada frekuensi 20 Hz dan 40 Hz, untuk mengatur kecepatan motor sebagai penggerak pompa dapat menghemat penggunaan energinya. Merugikan penurunan konsumsi energi sebesar 20,54% dan pengurangan biaya operasional hingga Rp. 3.292,32 per bulan pada implementasi motor sebagai penggerak pompa.